2022
DOI: 10.1136/bmjopen-2021-053085
|View full text |Cite
|
Sign up to set email alerts
|

What should pulmonary rehabilitation look like for people living with post-tuberculosis lung disease in the Bishkek and Chui region of the Kyrgyz Republic? A qualitative exploration

Abstract: ObjectiveAfter experiencing tuberculosis (TB), many people develop post-tuberculosis lung disease (PTBLD). Pulmonary rehabilitation (PR) centrally comprising of education and exercise is recommended internationally for people living with chronic respiratory diseases. However, no such service exists in Kyrgyzstan. This study investigated the opinions of healthcare professionals who would be expected to be potential future referrers to PR and adults living with PTBLD about what a PR programme could look like in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…Examples include rhythmic movements, singing and dance, volleyball and yoga. [151][152][153] Currently, little data exist to support whether such adaptations or adjuncts can enhance PR delivery either through improvement in core outcomes, or better completion rates.…”
Section: Cultural Adaptations To Prmentioning
confidence: 99%
“…Examples include rhythmic movements, singing and dance, volleyball and yoga. [151][152][153] Currently, little data exist to support whether such adaptations or adjuncts can enhance PR delivery either through improvement in core outcomes, or better completion rates.…”
Section: Cultural Adaptations To Prmentioning
confidence: 99%
“…It may be an important scientific development to consider the appropriate cultural adaptation of pulmonary rehabilitation in these settings [203,204]. Early work has been described in Kyrgyzstan for example where the fundamental principles of exercise training have been intertwined with singing and ball games after detail qualitative work to understand the needs of the post TB lung disease population [205].…”
Section: Pulmonary Rehabilitation: State Of the Science Sally Singh R...mentioning
confidence: 99%
“…Consequently, they are ostracized by family, friends, and their wider community, contributing to social isolation [23]. Similarly, people with posttuberculosis lung disease have described being outcast from their families and having difficulties finding employment because of ongoing public fears of infection, contributing to becoming withdrawn and feeling depressed [24 ▪ ]. Similar experiences have been reported by people with chronic respiratory disease in relation to coronavirus disease 2019 (COVID-19), such as experiencing abuse in reaction to cough [25].…”
Section: Stigmamentioning
confidence: 99%
“…people living with chronic respiratory disease and those supporting them) and services are needed while societal stigma continues. People with asthma have described how support groups can be important in helping reduce feelings of shame, and supporting acceptance of their condition [26], while people with posttuberculosis lung disease have suggested that services like pulmonary rehabilitation should include psychological support to help address these challenges [24 ▪ ]. Adjusting language used to describe conditions may be helpful: participants with asthma in a recent intervention development study felt a new approach using nonmedical language, re-framing asthma as involving a healthy mechanism being triggered too easily (rather than a deficiency or weakness), could reduce stigma and self-blame, potentially increasing motivation to adhere to treatments [33 ▪ ].…”
Section: Stigmamentioning
confidence: 99%